Effect of Curing Conditions on the Interface Strength of Single-Fibre Composite Specimens - Solmaz, Murat Yavuz; Kaman, Mete Onur; Turan, Kadir (Carl Hanser Verlag, 2012)
The purpose of this paper is to examine the effect of curing conditions on interface strength in single-fibre composites. Test specimens produced by using polyester resin and single glass fibre were cured under four different temperatures, which were room temperature, 40 degrees C, 55 degrees C and 70 degrees C for three different curing periods, which were 1 hour, 4 hours and 8 hours. Afterwards they were subjected to tensile test. As a result of the examination under optic microscope, it has been observed that the major damage formations are in the form of matrix cracks and fibre fragments. Young modulus and therefore mechanical properties of single-fibre composite specimens improved after a treatment above 40 degrees C.
Keywords: Fragmentation Test; Stress